Nadrabianie zaległości? O słowackich przekładach literatury polskiej (nie tylko) w 2017 roku - Obertová, Zuzana (Przekłady Literatur Słowiańskich, 2019)
The author of this paper characterizes the Polish literature translated into the Slovak language over the last few years with particular focus on the year 2017. Three genres have been translated the most: literary reportage, detective novel, and fantasy literature. What is underscored is the function of these translations in the receiving (Slovak) culture and literature, as well as the reception of the translations by scholars and readers.